Checklist for data collection on Nonglom fishing practices and fishers - Mam, Kosal (2024)
The purpose of the checklist is to guide the collection of information on current fishing access and its contribution to local livelihoods. The data and information generated will inform the Nonglom Management Committee’s decisions on regulating fishing access, establishing fish conservation zones, and defining how aquatic habitats and their connectivity can be reestablished. Iterative data collection will help establish trends in access, resources, and needs for aquatic habitat enhancement.